Methane emissions from gathering and boosting compressor stations in the U.S. Supporting volume 3: Emission factors, station estimates, and national emissions - Zimmerle, Daniel, author; Vaughn, Timothy, author; Luck, Benjamin, author; Lauderdale, Terri, author; Keen, Kindal, author; Harrison, Matthew, author; Marchese, Anthony, author; Williams, Laurie, author; Allen, David, author (Colorado State University. Libraries, 2019)
This section provides an overview of the field campaign for the entire project and the data collected in the field campaign data and during the analysis phase of the project.
Volume 3: Emission factors, station estimates, and national emissions
Emission factors, station estimates, and national emissions
October 2019 revision.
Authors are from: Energy Institute at Colorado State University, AECOM, SLR Consulting, Fort Lewis College, and University of Texas, Austin, Texas, USA.
Keywords: methane; emission factors; national model; greenhouse gases; gathering facilities